Oral lichen planus and lichenoid reactions: etiopathogenesis, diagnosis, management and malignant transformation - Ismail, Sumairi; Kumar, Satish K.S.; Zain, R.B. (Nihon University School of Dentistry, 2007)
Lichen planus, a chronic autoimmune, mucocutaneous disease affects the oral mucosa (oral lichen planus or OLP) besides the skin, genital mucosa, scalp and nails. An immune mediated pathogenesis is recognized in lichen planus although the exact etiology is unknown. The disease most commonly affects middle-aged females. Oral lichenoid reactions (OLR) which are considered variants of OLP, may be regarded as a disease by itself or as an exacerbation of an existing OLP, by the presence of medication (lichenoid drug reactions) or dental materials (contact hypersensitivity). OLP usually presents as white striations (Wickham's striae), white papules, white plaque, erythema, erosions or blisters. Diagnosis of OLP is established either by clinical examination only or by clinical examination with histopathologic confirmation. Direct immunofluorescence examination is only used as an adjunct to the above method of diagnosis and to rule out specific autoimmune diseases such as pemphigus and pemphigoid. Histopathologic features of OLP and OLR are similar with suggestions of certain discriminatory features by some authors. Topical corticosteroids are the treatment of choice for OLP although several other medications have been studied including retinoids, tacrolimus, cyclosporine and photodynamic therapy. Certain OLP undergo malignant transformation and the exact incidence and mechanisms are still controversial. In this paper, etiopathogenesis, diagnosis, management and malignant transformation of OLP and OLR have been reviewed.